Kekerasan Terhadap Perempuan dan Rekonstruksi Budaya - Rima, Febiana (Jurnal Etika Respons, 2009)
Violence against women manifests itself in many ways in our age. It could happen in family, in school, and in society at large. Especially in patriarchal culture, violence has its root in the doctrine that women and men are not equal. The natural differences of both were constructed into social relation that puts men on the highest position of power relation pyramid. Violence in this culture is an instrument to keep and protect the power of men. Searching thesolution to this social issue, this article promotes a political reconstruction that based on the universal declaration of human rights and political communication.